GOOD or BAD Responder? Behavioural and Neuroanatomical Markers of Clinical Response to Donepezil in Dementia - Gabriella Bottini; Manuela Berlingeri; Stefania Basilico; Serena Passoni; Laura Danelli; Nadia Colombo; Maurizio Sberna; Massimo Franceschi; Roberto Sterzi; Eraldo Paulesu (Behavioural Neurology)
We explored the neuropsychological and neuromorphometrical differences between probable Alzheimer's disease patients showing a good or a bad response to nine months treatment with donepezil. Before treatment, the neuropsychological profile of the two patient groups was perfectly matched. By the ninth month after treatment, the BAD-responders showed a decline of the MMSE score together with a progressive impairment of executive functions. A voxel-based morphometry investigation (VBM), at the time of the second neuropsychological assessment, showed that the BAD-responders had larger grey and white matter atrophies involving the substantia innominata of Meynert bilaterally, the ventral part of caudate nuclei and the left uncinate fasciculus, brain areas belonging to the cholinergic pathways. A more widespread degeneration of the central cholinergic pathways may explain the lack of donepezil efficacy in those patients not responding to a treatment that operates on the grounds that some degree of endogeneous release of acetylcholine is still available.